English The Parents’ Role in Paired Reading (PR) Method for Fifth-Graders Reading Ability at Madrasah Ibtidaiyah (MI) - Ekaningsih, Nur; Nafisa, Naela Ainun; Ekaningsih, Ekaningsih (Universitas Nusantara PGRI Kediri, 2022)
The researcher’s goal is to elaborate in detail on the parents’ role and explain the steps of parents’ role in the Paired Reading (PR) method for fifth-graders reading ability. The researcher carried out the qualitative approach, which describes the data after observations. A total of five parents were involved in this research as a participant. Data were collected by using interviews on Whatsapp with ten questions for each parent as a participant in this research. The findings indicated that parents have a crucial role in assisting their children in improving their reading ability. They played their role as teachers, motivators, and facilitators. Parents acted as a teacher to provide examples of correct pronunciation. Then, working as a motivator to motivate their children in English reading was fun and useful. Finally, parents acted as a facilitator by providing a comfortable learning environment. Therefore, parents’ role in the Paired Reading (PR) method is considered effective in improving children reading ability. Keywords:Parents’ Role, Paired Reading (PR) Method, Reading Ability